2019
DOI: 10.22159/ijpps.2019v11i3.29388
|View full text |Cite
|
Sign up to set email alerts
|

Case Study on Beta Blockers Induced Psoriasis

Abstract: Drug-induced Psoriasis is one among the common etiological factors of Psoriasis reported worldwide. Familiar drugs known to cause psoriasiform eruptions include Anti-malarials, Beta blockers, NSAIDs, Lithium. etc. Certain antihypertensives like ACE inhibitors, diuretics are also documented to have caused psoriatic episodes. A 57 y old South-Indian male patient with a history of Hypertension, Diabetes Mellitus, Atrial Fibrillation for 4 y; was on antihypertensive therapy for Hypertension and Atrial Fibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The name is derived from the Greek word psora which means to itch [2]. Psoriasis is defined on a clinical basis as chronic, relapsing, remitting papulosquamous eruption with typical localization on the extensor surfaces such as elbows and knees involving scalp, genitalia or nails, and other sites [3]. Among the psoriasis patients, the ratio of male to female was 1.1:1.…”
Section: Introductionmentioning
confidence: 99%
“…The name is derived from the Greek word psora which means to itch [2]. Psoriasis is defined on a clinical basis as chronic, relapsing, remitting papulosquamous eruption with typical localization on the extensor surfaces such as elbows and knees involving scalp, genitalia or nails, and other sites [3]. Among the psoriasis patients, the ratio of male to female was 1.1:1.…”
Section: Introductionmentioning
confidence: 99%
“…Though the therapeutic property of this plant was known to the Kani tribe of Kerala inhabiting in the Agasthya hills of the Western Ghats, its medicinal properties were never known to the outside world until Pushpangadan et al revealed about it in 1988 [5]. Further scientific investigations reported the plant as an adaptogenic [5], antimicrobial [6], antioxidant [7], anti-fatigue [5], immune enhancing, cardioprotective [8], antidiabetic [9], hepatoprotective [10], anti-nociceptive [11] and anti-inflammatory herb. Being an important ethnomedicinal herb, so far, no study has been carried out on anticancer analysis of leaves of T. zeylanicus.…”
Section: Introductionmentioning
confidence: 99%
“…Various secondary metabolites including phenolic compounds, flavonoids, and terpenoids are being explored as anti-AD agents. [14] Curcumin, a natural polyphenol extracted from Curcuma longa (Zingiberaceae), acts as an antioxidant, anti-neuroinflammatory, and anti-aggregative agent in the treatment of AD. [15][16][17][18][19][20] Similarly, α-bisabolol is a naturally occurring sesquiterpene isolated from the blossoms of chamomile (Matricaria chamomilla; Asteraceae) by Isaac and collaborators in 1951 [21] possesses diverse ethnomedicinal properties, such as antimicrobial, antioxidant, anti-inflammatory, anticancer, and anti-cholinesterase properties.…”
mentioning
confidence: 99%